Cyclin-D1 Utility in Classification of Endometrial Stromal Sarcomas and Segregation from other Uterine Sarcomas - Zahra, Kanwal; Khalid, Ahmareen; Khurshid, Shaista; Zafar, Ghazal; Tanwani, Kumar (International Journal of Pathology, 2018)
Context: Endometrial stromal sarcomas (ESSs) are rare mesenchymal tumors of uterus which accounts for less than 10% of all uterine sarcomas. Gene rearrangement studies unveil their genetic heterogeneity with the discovery of specific YWHAE-FAM22 gene fusion. According to recent WHO classification of endometrial stromal tumors all Endometrial stromal sarcomas with this fusion are labeled as high grade-Endometrial Stromal Sarcomas (HG-ESS). Immunohistochemically HG-ESSs with YWHAE- FAM22 translocation express nuclear Cyclin D1 positivity which can be used as a surrogate immunohistochemical marker for this translocation.Objective: Determine diagnostic utility of Cyclin D1 as a marker to segregate high grade- Endometrial Stromal Sarcomas (HG-ESS) from low grade-Endometrial Stromal Sarcomas (LG-ESS) and undifferentiated uterine sarcoma (UUS) and from other uterine sarcomas including leiomyosarcomas and carcinosrcomas.Materials and Methods: Cases of Endometrial stromal sarcomas, leiomyosarcomas and carcinosarcomas received from Jan 2010- Jan 2015 were reviewed and immunostained with Cyclin D1, CD-10, ER, PR and Desmin. Nuclear positive or negative staining for Cyclin D1 was noted.Results: Total 36 cases of uterine sarcomas including 10 cases of ESS, 20 cases of leiomyosrcoma and 6 cases of carcinosarcoma were retrieved from surgical database. Out of ten cases of endometrial stromal sarcomas, five were low grade, two were high grade and three were undifferentiated sarcomas. Cyclin D1 was expressed in three cases previously diagnosed as low grade, high grade and undifferentiated sarcomas respectively. Cyclin D1 positive undifferentiated uterine sarcoma (UUS) also revealed diffuse CD-10 positivity. Other two cases with a positive Cyclin D1 expression revealed a patchy CD-10 positivity. Negative expression of Cyclin D1 was noted in all cases of leiomyosrcoma and carcinosarcoma.Conclusions: Endometrial stromal sarcomas are relatively uncommon tumors and can pose diagnostic problems for pathologists. Smooth muscle tumors (leiomysrcomas) and carcinosarcomas are among the top differentials. Final diagnosis usually requires immunohistochemistochemical analysis with a panel of immunomarkers. Cyclin D1 expression along with patchy CD-10 positivity favors HG-ESS over LG-ESS and UUS. Cyclin D1 positivity along with diffuse CD-10 expression favors Undifferentiated Uterine Sarcoma. Negative expression in other uterine sarcomas makes it a specific marker for ESSs. It is suggested that Cyclin D1 along with CD-10, ER, PR and Desmin should be added in immunohistochemical panel of high grade uterine sarcomas especially if patchy expression of CD-10 is noted. It is to make a provisional diagnosis of YWHAE-FAM22 associated HG-ESS when fluorescence in situ hybridization (FISH) and reverse transcriptase polymerase chain reaction (RT-PCR) are not available to make a final diagnosis.